2012
DOI: 10.3844/ajessp.2012.152.157
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide use in South and South-East Asia: Environmental Public Health and Legal Concerns

Abstract: Problem statement: The South and South East Asian countries are characterized by their rich biodiversity as well as cultural diversity. Agricultural expansion for livelihood security is leading to an increase in pesticide application in this region. It has been observed that because of the hot and humid conditions prevalent in this region, most farmers and pesticide applicators do not use proper protective gear, thereby exposing themselves to the hazards of pesticide poisoning. Another important issue is the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Another concern is that this study was conducted in only chlorpyrifos, cypermethrin, paraquat, and glyphosate. These four pesticides are widely used in agriculture, especially in Southeast Asia (Gupta, 2012;Sapbamrer, 2018;Tawatsin et al, 2015). However, agricultural workers may apply several products of pesticides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another concern is that this study was conducted in only chlorpyrifos, cypermethrin, paraquat, and glyphosate. These four pesticides are widely used in agriculture, especially in Southeast Asia (Gupta, 2012;Sapbamrer, 2018;Tawatsin et al, 2015). However, agricultural workers may apply several products of pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that agricultural workers are more vulnerable than typical non-agricultural workers because they face a greater risk of exposure to pesticides (Damalas & Koutroubas, 2016). Chlorpyrifos and cypermethrin are routinely used as insecticides in agriculture, while paraquat and glyphosate are widely used as herbicides, especially in Southeast Asia countries including Thailand (Gupta, 2012;Sapbamrer, 2018;Tawatsin et al, 2015). Pesticide exposure occurs mainly during mixing, loading and application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority (56.7%) of them did not maintain extension media contact for farming activities and about threefourths (76%) of them had no connection with any organization. The research findings of Gupta (2012) explored that the majority of the farmers did not communicate with extension agents for conducting farming practices. Nonetheless, a significant portion (46%) of the respondents had medium knowledge and almost half (48.7%) of them had a less favourable attitude towards the effects of excessive use of agrochemicals whereas about two-third (67.3%) of them were unaware regarding the effects of excessive use of agrochemicals on farming practices which a matter of concern and presented in Table 1.…”
Section: Socio-economic Attributes Of the Respondentsmentioning
confidence: 99%
“…Conducting farming practices effectively and efficiently could be a useful strategy in eradicating poverty and hunger which is the key indicators of sustainable development (FAO, 2021). To produce more crops from small landholdings and feed the large population, farmers especially in developing countries are applying agrochemicals in their farming practices (Gupta, 2012). Agrochemicals are the chemical compounds (fertilizer, pesticides, hormone, fungicides, insecticides, herbicides etc.)…”
Section: Introductionmentioning
confidence: 99%